2006
DOI: 10.1063/1.2204474
|View full text |Cite
|
Sign up to set email alerts
|

Confined Dynamics in Nanophase-Separated Side Chain Polymers

Abstract: The relaxation behavior of different series of nanophase-separated side chain polymers with long alkyl groups is studied and compared with corresponding results from the literature. Characteristic for these homopolymers is that alkyl groups -belonging to different monomeric units and chains -aggregate to alkyl nanodomains with a typical dimension of about 0.5-2 nm. Relaxation spectroscopy data and calorimetric results show that a polyethylene-like glass transition (α PE ) occurs within these alkyl nanodomains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…It is believed that the key to obtain tailor-made materials is the understanding of the interplay between structure and dynamics in the system. In this direction, a large effort has been devoted in the last years to characterize and to relate the structural and dynamical properties in families of polymers with alkyl side groups, like, e.g., poly­( n -alkyl methacrylates) (PnMAs), poly­( n -alkyl acrylates), ,, poly­(di- n -alkyl itaconates), poly­(3-alkyl thiophenes) (P3ATs), , rod polyimides, polyazomethynes, poly­( p -phenylene–terephthalates), , or poly­(α- n -alkyl β- l -aspartates) . The most spectacular effect of varying the microstructure by increasing the side-group length in these systems is a dramatic plasticization effect: a strong decrease of the value of the glass-transition temperature T g .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the key to obtain tailor-made materials is the understanding of the interplay between structure and dynamics in the system. In this direction, a large effort has been devoted in the last years to characterize and to relate the structural and dynamical properties in families of polymers with alkyl side groups, like, e.g., poly­( n -alkyl methacrylates) (PnMAs), poly­( n -alkyl acrylates), ,, poly­(di- n -alkyl itaconates), poly­(3-alkyl thiophenes) (P3ATs), , rod polyimides, polyazomethynes, poly­( p -phenylene–terephthalates), , or poly­(α- n -alkyl β- l -aspartates) . The most spectacular effect of varying the microstructure by increasing the side-group length in these systems is a dramatic plasticization effect: a strong decrease of the value of the glass-transition temperature T g .…”
Section: Introductionmentioning
confidence: 99%
“…The structural and dynamical properties of homopolymers with long alkyl side groups, like the families of poly( n -alkyl methacrylates) (PnMAs), poly( n -alkyl acrylates) (PnAs), ,, and poly(di- n -alkyl itaconates), have been extensively studied during the past decades. On the basis of X-ray diffraction, it has been suggested that side groups of different monomeric units tend to aggregate forming self-assembled alkyl nanodomains [called polyethylene (PE)-like nanodomains]. ,, From a dynamical point of view, these materials show a rich variety of relaxational processes, and the existence of two different glass transitions was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, particular interest has been focused on the structural and dynamical features of the family on poly( n -alkyl methacrylates) (PnMAs) and other polymers containing alkyl side groups. ,− The main reason is the suggested formation of nanodomain structures by self-assembly of the side groups, that are segregated at nanometric scale from the main-chain subsytems. Such a morphology was deduced from the presence in the X-ray diffraction patterns of peaks at relatively low Q -values (“intermediate”-range), with side-group length dependent positions. ,, Later, neutron diffraction combined with isotopic labeling definitely proved such a scenario. , In addition, interesting confinement effects on the dynamics of the side groups have been reported, ,, in principle attributed to confinement effects induced by the surrounding main chains.…”
Section: Introductionmentioning
confidence: 99%